Corrigendum: Pavlović M, Đurić A, Stevanović I, Begić A, Vujanović D, Ninković M, Đukić M. Disulfiram partially improves oxidative but not androgen status in rats exposed to cadmium. Arch biol sci. 2019;71(4):747-53 - team, Editorial (Archives of Biological Sciences, 2020)
https://doi.org/10.2298/ABS200226010E The authors of the article: Pavlović M, Đurić A, Stevanović I, Begić A, Vujanović D, Ninković M, Đukić M. Disulfiram partially improves oxidative but not androgen status in rats exposed to cadmium. Arch Biol Sci. 2019;71(4):747-53 have informed the Editorial Office of the error in the position of the author D. Vujanović, who should be at the end of the list of authors and replaced with M. Đukić. The authors have requested for this error to be corrected. Therefore, the journal is publishing this Corrigendum. The authors of this article should be listed as follows: Pavlović M, Đurić A, Stevanović I, Begić A, Đukić M, Ninković M, Vujanović D. Link to the corrected article 10.2298/ABS190814057P